Towards a Paradigm Shift: Analysis of Student Teachers’ and Teacher Education Institutions’ Readiness on Kurikulum Merdeka - Kurnia Putri Sepdikasari Dirgantoro; Robert Harry Soesanto (Jurnal Pendidikan dan Kebudayaan, 2023)
This research is to examine the preparedness and initiatives of Teacher Training and Education Institutes (LPTK) and student teachers in implementing Kurikulum Merdeka. This cross-sectional study employs a phenomenological approach. The study encompasses 448 student teachers from various provinces in Indonesia. Data were gathered through a questionnaire featuring open-ended questions, and the results were analyzed using a multistage descriptive coding and pattern approach. The findings reveal that 82.81% of student teachers are ready to implement Kurikulum Merdeka. However, in terms of understanding, 24.55% of them still need to improve their understanding about the new curriculum. In conclusion, there persists a need to continually enhance the knowledge and skills of student teachers in navigating the implementation of Kurikulum Merdeka. Additionally, LPTK must ensure the provision of competencies adequately.